Manipulation of the halloysite clay nanotube lumen for environmental remediation: a review. Issue 3 (8th February 2022) - Li, Ying; Yuan, Xingzhong; Jiang, Longbo; Dai, Huan; Zhao, Yanlan; Guan, Xian; Bai, Jing; Wang, Hou
Abstract : The halloysite clay nanotube lumen has shown great application potential in the field of environmental remediation. This relies on delicate manipulation of the clay nanotube lumen and benefits from the unique functionality of the nanotube lumen. Abstract : Halloysite nanotubes (HNTs) are a naturally occurring clay mineral that have attracted much attention in recent years. Manipulating the lumen of halloysite nanotubes to take full advantage of their unique functions ( i.e., nano-containers, nano-channels, nano-reactors) is the frontier of halloysite research. This article reviews the manipulation techniques of the halloysite lumen from three aspects: surface modification, chemical loading and metallics embedding. On this basis, the application of manipulating the halloysite lumen in various branches of environmental remediation, such as adsorption, filtration, sustained release, catalysis, and multifunctional synchronization, is further summarized. It is emphasized that the acid-etched halloysite lumen can be used as a nano-tubular adsorbent with good adsorption performance for organic pollutants. The organo-modified halloysite lumen has the potential not only as a nano-tubular adsorbent for organic pollutants, but also as a membrane nanofiller for the precise separation of specific molecules. The loading and sustained release of environmental chemicals ( e.g., remediators, pesticides, fertilizers) by the halloysite lumen can reduce environmental hazards regarding their indiscriminate use. The halloysite lumen embedded with small-sized metallic nanoparticles (NPs) can be used as a sintering-resistant, high-performance and durable "nano-confined catalyst", and can also be further processed into dual-functional nanocomposites ( e.g., catalysis/detection synchronization, adsorption/separation synchronization). Finally, the challenges of halloysite lumen manipulation technology and the further application perspectives of manipulating the halloysite lumen for environmental remediation are proposed.